Epidermal Growth Factor (EGFR) copy number aberrations in esophageal and gastro-esophageal junctional carcinoma. Issue 1 (December 2015) - Dahle-Smith, Åsa; Stevenson, David; Massie, Doreen; Murray, Graeme; Dutton, Susan; Roberts, Corran; Ferry, David; Osborne, Aileen; Clark, Caroline; Petty, Russell; Miedzybrodzka, Zosia
Abstract Background Clinical trials of agents targeting epidermal growth factor receptor (EGFR) in esophageal carcinoma (EC) have indicated a minority subgroup responsive to anti-EGFR therapies. Other investigations suggest increases in EGFR copy number are associated with poor prognosis in EC, but have used a variety of different techniques and tested numbers remain small. A validated assay for EGFR copy number in EC is needed, to allow investigation of EGFR copy number gain as a predictive biomarker for the anti-EGFR responsive subgroup of patients. We developed a scoring system in EC based upon established systems for EGFR fluorescence in-situ hybridisation (FISH) in lung cancer, and applied this in a series of 160 UK patients with advanced EC. Results Dual colour FISH on formalin fixed paraffin embedded (FFPE) biopsies were scored independently by two operators as: disomy (score = 1), low trisomy (score = 2), high trisomy (score = 3), low polysomy (score = 4), high polysomy (score = 5) and amplification (score = 6). EGFR FISH positive cases (scores 5 and 6) were found in 32/160 (20 %) tumours, with high polysomy in 22 (13.8 %) and amplification in 10 (6.3 %). Two independent operator scores for FISH positivity were 100 % concordant. EGFR FISH positive status was not associated with clinic-pathological features. EGFR amplification was associated with worse survival (HR = 2.64, 95 % CI 1.04 to 6.71, p = 0.03). Conclusion Our FISH scoring system for EGFR in advanced EC identifies a significant subgroup (20.0 %) of FISH positive patients. EGFR amplification, which is found in 6.3 %, is associated with poor survival. It is not known if there is a role for EGFR targeted treatment in this subgroup of patients, however we are now utilising this EGFR FISH assay and scoring system in biopsies from clinical trials utilising anti-EGFR targeted therapies.